Innovation for the 21st century harnessing the power of intellectual property and antitrust law - Carrier, Michael A. (Oxford : Oxford University Press, 2009)
'Innovation For The 21st Century' contends that intellectual property and antitrust, the two most important laws fostering innovation, are not being used most effectively to achieve this goal and offers various proposals that individually and collectively remedy this deficiency.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Intellectual property -- United States; Antitrust law -- United States